Prevention of Earnings Management through Audit Committee and Audit Quality in the Award-Winning and Non-Winning Companies - Iriyadi Iriyadi (Universitas Syiah Kuala, 2019)
Objective – The purpose of this study is to determine the role of the audit committee and the quality of external audits on the prevention of earnings management. Design/methodology – The study was conducted using data from 34 winning and non-winning companies for Annual Report Awards (ARA) and Good Corporate Governance (GCG) Awards in 2008-2011, the period of the global economic crisis after the Enron and Worldcom cases in 2002 which triggered the strengthening of the role of the audit committee and external audit. Results – This study found that two important components of the corporate governance structure; audit committee, and external audit, did not affect earnings management. However, by adding the Award control variable, it shows that there is a difference in the effect on earnings management between winners and non-award winners. It suggest that shareholders must continue to strengthen the role of the audit committee and external audit because earnings management is behavior and opportunity for management to deliberately change financial statements that are not easily proven except in very material quantities and over a period of several years. In addition, shareholders, creditors, and regulators should require company management to take part in ARA and GCG Award competitions. Research limitations/implications – The limitation of this study is the small number of samples and the relatively short period of only two years.